On oscilation and asymptotic behaviour of solutions of one system of differential-functional equations of neutral type - Ivanov , A. F.; Marushiyak , P. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Conditions for the oscillation of all solutions and for the existence of nonoscillatory solutions with polynomial growth at infinity are given for the system of differential-functional equations of neutral type \(d^n dt^n [x(t) + λ _1 x(t - τ _1 )] = p(t)f(y(θ _1 (f)), d^n dt^n [y(t) + λ _2 y(t - τ _2 )]q = (t)g(x(θ _2 (t)), 0 |λ _1 |,|λ _2 |< 1. \)